CD160 Plays a Protective Role During Chronic Infection by Enhancing Both Functionalities and Proliferative Capacity of CD8+ T Cells - Zhang, Linxia; Zhang, Anli; Xu, Jun; Qiu, Chao; Zhu, Lingyan; Qiu, Chenli; Fu, Weihui; Wang, Ying; Ye, Lilin; Fu, Yang-xin; Zhao, Chen; Zhang, Xiaoyan; et al. (Frontiers in Immunology, 2020)
The understanding of protective immunity during HIV infection remains elusive. Here we showed that CD160 defines a polyfunctional and proliferative CD8+ T cell subset with a protective role during chronic HIV-1 infection. CD160+CD8+ T cells derived from HIV+ patients correlated with slow progressions both in cross-sectional study and in a 36-month longitudinal cohort, displayed enhanced cytotoxicity and proliferative capacity in response to HIV Gag stimulation; triggering CD160 promoted their functionalities through MEK-ERK and PI3K-AKT pathways. These observations were corroborated by studying chronic lymphocytic choriomeningitis virus (LCMV) infection in mice. Genetic ablation of CD160 severely impaired LCMV-specific CD8+ T cell functionalities and thereby resulted in loss of virus control. Interestingly, transcriptional profiling showed multiple costimulatory and survival pathways likely to be involved in CD160+ T cell development. Our data demonstrated that CD160 acts as a costimulatory molecule positively regulating CD8+ T cells during chronic viral infections, thus representing a potential target for immune intervention.